2013
DOI: 10.1007/s12070-013-0660-8
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathological Study of 100 Patients of Hoarseness of Voice: In a Rural Based Hospital

Abstract: Hoarseness of voice is one of the commonest symptoms in otolaryngological practice and it indicates diseases ranging from totally benign condition to the most malignant condition. This is a study to know the etiology, predisposing factor, and clinical profile of patients having hoarseness of voice. The study was carried out in the department of ENT, Mahatma Gandhi Institute of Medical Sciences, Sewagram. Patients coming to our OPD were selected. All the patients then underwent detailed history and routine inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 11 publications
10
24
0
Order By: Relevance
“…This is in accordance with findings in other studies [19][20]. In this present study, smoking and alcohol were less common predisposing factors compared to other previous study [16].…”
Section: Discussionsupporting
confidence: 94%
“…This is in accordance with findings in other studies [19][20]. In this present study, smoking and alcohol were less common predisposing factors compared to other previous study [16].…”
Section: Discussionsupporting
confidence: 94%
“…Postoperative sore throat and hoarseness associated with tracheal intubation can be influenced by many other factors, such as gender 28 ; size, 29 cuff type, 30 and intra-cuff pressure 31 of tubes; and type 10 or duration 32 of surgery. Among these factors, sore throat may be more directly affected by the physical damage resulting from intubation itself, 7 15 17 whereas hoarseness seems to be more associated with other factors such as smoking history 33 or duration of intubation, 32 which were similar between the two groups. Therefore, thermal softening of DLTs seems to influence the incidence of postoperative sore throat but not hoarseness, which again suggests a reduction in laryngeal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Pal, et al 10 found smoking habit in 33% cases with hoarseness. This could be explained by the fact that majority of our patients are having malignant lesions as compared to Pal study whose majority patients are having benign lesions.…”
Section: Authormentioning
confidence: 96%